Marketing Strategy for Coconut Brown Sugar to Improve Community Welfare in Pasiang Village: JEL Classification: Q13, M31, Q12, I31, O18 - Peri Peri; Nining Diah Andayani; Halbi Halbi (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study examines the marketing strategies of coconut brown sugar and their implications for the welfare of artisans in Pasiang Village, Matakali District, Polewali Mandar Regency. The study employed a descriptive qualitative approach using a case study. The research location was purposively selected, with 36 informants consisting of producers, collectors, suppliers, retailers, and consumers. Data were collected through observation, interviews, questionnaires, and documentation and analyzed using the Miles and Huberman model. Marketing strategies were formulated through SWOT analysis using IFAS and EFAS matrices. The results show that coconut brown sugar marketing remains traditional and involves three marketing channels with several marketing institutions. The Producer-Supplier-Retailer-Consumer channel is the most efficient because it provides producers with a higher selling price than other channels. The SWOT analysis produced an IFAS score of 2.82 and an EFAS score of 2.62, placing the business in Quadrant I and indicating an aggressive growth strategy. Recommended strategies include improving product quality, expanding market share, utilizing digital marketing, developing efficient distribution channels, and strengthening producer institutions. These strategies can enhance product competitiveness, expand market access, increase artisan income, and ultimately improve the welfare of coconut brown sugar artisans in Pasiang Village.